The Effectiveness Of Group Guidance Using Acceptance And Commitment Therapy (Act) Techniques To Increase Students' Physical Self-Acceptance At Imelda Junior High School - Anissa, Nur; Siregar, Alfin (UNIVERSITAS PAKUAN, 2025)
This study aims to examine the implementation of group counseling services using the Acceptance and Commitment Therapy (ACT) technique to improve students’ physical self-acceptance. The research employed a Quasi-Experimental approach with a Pre-Test Post-Test Control Group Design. The participants consisted of 16 eighth-grade students of SMP Imelda Medan, divided into two groups: 8 students in the experimental group and 8 students in the control group, selected using purposive sampling. The results of the Paired Sample T-Test showed a significant difference between the experimental and control groups, with a significance value of 0.000 < 0.05. Thus, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This indicates that group counseling using the ACT technique is effective in improving students' physical self-acceptance. The average pre-test score in the experimental group was 79.13, which increased to 102.75 in the post-test. Meanwhile, the control group’s pre-test average was 78.25 and post-test average was 85.75. The increase in post-test scores indicates a significant improvement in physical self-acceptance